Toxic Effects of Sapium indicum (Willd.) Fruits on Animal Model - Md Sayedur Rahman; Tahmina Monowar (International Journal of Phytomedicine, 2014)
The present study deals with toxic effects of petroleum ether (40°-60°C) and water-soluble alcoholic extracts of the fruits of Sapium indicum (Willd.) on laboratory animal model. The petroleum ether (40°-60°C) extract administered through intravenous route in mice, and through oral routes in rats exhibited toxic effects. The 24-hr LD50 value of the extract was found as 816.58 µg.kg-1 and 208.93 mg.kg-1 body weight in mice and rats, respectively. On the other hand, the experimental rats treated orally with the water-soluble alcoholic extract exhibited no mortality. The results revealed that the petroleum ether (40°-60°C) extract of the fruit is more toxic than organochlorine compounds having a prospect of using it as an alternative source of bio-pesticides.